Superhydrophobic, Oleophobic, Self-Cleaning Flexible Wearable Temperature Sensing Device. (4th August 2022) - Chen, Chen-Han; Tsai, Ting-Wei; Cheng, I-Chun; Chen, Jian-Zhang
Abstract : We use a poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/carbon nanotube (CNT) composite as the temperature sensing layer, and the device exhibited a high sensitivity of −2.46%/°C. A sandpaper-molded PDMS with fluorinated surface modification protection layer is used as the superhydrophobic, oleophobic, self-cleaning protective encapsulation layer. This device exhibits a self-cleaning function when it makes contact with liquids such as water, tea, coffee, and milk. In addition, the surface can also repel liquids with low surface tension (such as oil), exhibiting good oleophobicity. Resistance to ultrasonication in an organic solvent for 120 min and a 400-cycle tape peel test reveal durability of this device. The device functions under similar conditions after 1000 bending cycles with a bending radius of 0.875 mm. In this work, we demonstrate a simple and low-cost technique to fabricate durable and wearable temperature sensing devices.